Buoyancy effects on the flows around flat and steep street canyons in simplified urban settings subject to a neutral approaching boundary layer: Wind tunnel PIV measurements - Zhao, Yongling; Li, Haiwei; Kubilay, Aytaç; Carmeliet, Jan (The Science of the total environment, 2021)
The present wind tunnel particle image velocimetry (PIV) measurements document flows around flat and steep street canyons subject to thermal conditions at different levels, ranging from the Richardson number of 0.31 to 2.07. A steepness ratio, that is, the ratio of windward and leeward building heights, is proposed to characterise the geometrical influence of street canyons surrounded by buildings of non-uniform height. To study the thermal effects of building façades and ground on surrounding flow, surfaces of building models and the ground between them are heated up and maintained at three different temperatures to induce buoyant flows of different strength. The transition of the canyon flow from the typical rooftop shear-layer driven vortex to the buoyant plume type of flow is clearly revealed from the measurement results, which enhances the air removal that takes place at the roof-level of the two canyons. However, due to the different steepness of the canyons, the air removal rate from the steep canyon of a steepness ratio 2.52 is approximately 50% of that from the flat canyon with a steepness ratio of 1.53 in the buoyant plume-driven case because the downward flush flow along the windward façade suppresses the ascending plumes in the steep canyon. At the pedestrian level, the wind field is jointly dominated by the interplay between canyon-wide vortical flow and the buoyant plume rising ascending from the ground. The dynamics of non-isothermal flow in flat and steep canyons are revealed in detail, the implication of which is that the steepness of street canyons has to be considered in urban morphology planning, as well as in simplified geometrical representations of street canyons and in simplified urban canopy models. [Display omitted] •Non-isothermal flows around flat and steep canyons are studied using PIV measurements.•A steepness ratio is adopted to characterise the flow around steep canyons.•The transition from a shear-layer driven flow to a buoyant plume-driven flow enhances air removal.